2006
DOI: 10.1021/bp050400w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Porous Magnetic Silica Microspheres as Adsorbents for Isolation of Genomic DNA

Abstract: An improved procedure is described for preparation of novel mesoporous microspheres consisting of magnetic nanoparticles homogeneously dispersed in a silica matrix. The method is based on a three-step process, involving (i) formation of hematite/silica composite microspheres by urea-formaldehyde polymerization, (ii) calcination of the composite particles to remove the organic constituents, and (iii) in situ transformation of the iron oxide in the composites by hydrogen reductive reaction. The as-synthesized ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…Then through the reaction of iminodiacetic acid (IDA) with 3-glycidoxypropyltrimethoxysilane (GLYMO), which is immobilized on the prepared magnetic silica nanospheres charged with Zn 2+ , the magnetic nanospheres can be used to separate a model protein mixture [19]. Other synthetic methods for porous silica microspheres have been reported such as that described by Zhang et al in which hematite/silica composite microspheres are prepared by urea-formaldehyde polymerization of the composite particles to remove the organic components and the iron oxide in the composites is in situ transformed by hydrogen reductive reaction [20]. Gao et al reported the synthesis of porous silica-encapsulated magnetic nanoparticles as a nano-absorbent using a modified microemulsion technique.…”
Section: Magnetic Solids: Synthesis and Characterizationmentioning
confidence: 99%
“…Then through the reaction of iminodiacetic acid (IDA) with 3-glycidoxypropyltrimethoxysilane (GLYMO), which is immobilized on the prepared magnetic silica nanospheres charged with Zn 2+ , the magnetic nanospheres can be used to separate a model protein mixture [19]. Other synthetic methods for porous silica microspheres have been reported such as that described by Zhang et al in which hematite/silica composite microspheres are prepared by urea-formaldehyde polymerization of the composite particles to remove the organic components and the iron oxide in the composites is in situ transformed by hydrogen reductive reaction [20]. Gao et al reported the synthesis of porous silica-encapsulated magnetic nanoparticles as a nano-absorbent using a modified microemulsion technique.…”
Section: Magnetic Solids: Synthesis and Characterizationmentioning
confidence: 99%
“…In general, Fe 3 O 4 /silica composites are mostly prepared in solution or by sol-gel process [43][44][45][46][47][48][49]. However, the synthesis in solution needs many steps, even in sol-gel routes, where the formation requires calcination processes of high temperature and it is difficult to control the size and morphologies of the final products.…”
Section: Characterization Of the Synthesized Fe 3 O 4 /Silica Nmsmentioning
confidence: 99%
“…Up to date, many methods have been reported for coating metal oxide with silica including sol-gel process [38][39][40], microemulsion [41], and solution reaction [42]. Recently, Wan et al reported the synthesis of porous Fe 3 O 4 /silica microspheres by formation of ␣-Fe 2 O 3 /silica composite microspheres by ureaformaldehyde polymerization and then calcination in situ transformation of the iron oxide in the composites by hydrogen reductive reaction [43]. Kim's group demonstrated the preparation of Fe 3 O 4 /silica core/shell NPs by using reverse micelles as nanoreactors [44].…”
Section: Introductionmentioning
confidence: 99%
“…Silica has been considered as one of the most ideal materials for protecting Fe 3 O 4 NPs due to its reliable chemical stability, biocompatibility and versatility in surface modification [7]. It is anticipated that incorporating silica coating on a magnetic core could attain the advantage of silica and without sacrificing the unique magnetization characteristics of Fe 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%